2016
DOI: 10.1063/1.4966666
|View full text |Cite
|
Sign up to set email alerts
|

Optical metasurfaces for subwavelength difference operations

Abstract: Coupled metal nanostructures supporting localized surface plasmon resonances are represented as a nanoscale optical circuit that takes light fields as inputs and forms linear combinations of them with complex coefficients. The subwavelength arrays of these circuits form a metasurface that performs mathematical operations in two dimension on an incident light field. We demonstrate this concept with subwavelength scale plasmonic circuits that perform difference operations. The metasurface is fabricated from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…[25][26][27][28][29] These two points suggest that we should be able to directly translate the chiral operation of a single oligomer into a homogenized metasurface platform. So we also explore arrays of oligomers, as to show relevance of these concepts toward pursuit of plasmonic metasurfaces for polarization control, and other applications for flat optics [30][31][32][33] that capitalize on 2-dimensional fabrication. The single oligomer experiments in Figures 1, 3 and 4 have shown that each oligomer scatters light significantly more efficiently for either RCP or LCP, and these differences in scattering can generally be expected to affect the radiative coupling strength between an oligomer and its neighbors in the surrounding lattice.…”
Section: Doi: 101002/lpor201700216mentioning
confidence: 99%
“…[25][26][27][28][29] These two points suggest that we should be able to directly translate the chiral operation of a single oligomer into a homogenized metasurface platform. So we also explore arrays of oligomers, as to show relevance of these concepts toward pursuit of plasmonic metasurfaces for polarization control, and other applications for flat optics [30][31][32][33] that capitalize on 2-dimensional fabrication. The single oligomer experiments in Figures 1, 3 and 4 have shown that each oligomer scatters light significantly more efficiently for either RCP or LCP, and these differences in scattering can generally be expected to affect the radiative coupling strength between an oligomer and its neighbors in the surrounding lattice.…”
Section: Doi: 101002/lpor201700216mentioning
confidence: 99%
“…Nanophotonic, all-optical image processing methods on the other hand offer ultra-compact, real time and low power consumption alternatives for use in emerging integrated analogue optical computing and image processing devices [8,9]. There has been considerable recent interest in the use of metasurfaces or subwavelength gratings for optical information processing [9][10][11][12][13]. Attention has focussed on optical computing of spatial differentiation although experimental demonstrations have been limited and restricted to operations in one dimension [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in a recent work [2] it was theoretically shown that a metamaterial layer with a specially designed structure enables performing the operations of differentiation and integration of an optical beam with respect to a spatial coordinate. In the second group (resonant structure approach), various resonant diffractive structures including systems of multiple homogeneous layers [4][5][6][7][8][9][10], plasmonic circuits [11,12], and resonant diffraction gratings [13][14][15] are used. The possibility to utilize such resonant structures for optical differentiation or integration is based on the fact that the Fano profile describing the reflection or the transmission coefficient of the structure in the vicinity of the resonance can approximate the transfer function of a differentiating or integrating filter [4,5,13].…”
Section: Introductionmentioning
confidence: 99%